PENGEMBANGAN KOMPETENSI MENYIMAK DENGAN MODEL CD PEMBELAJARAN INTERAKTIF - Yuwono, Agus (Lembaran Ilmu Kependidikan, 2008)
Correct reading news represent one of the interest correct reading at KTSPJavanese SMP. At its execution of attainment of interest correct reading student still isoften met with klasikal method, so that study read lose looks. Therefore require tocreate atmosphere management of pleasant study and as according to abilitystorey;level or student interest in correct reading. Therefore this research aim to todevelop study media in the form of CD interaktif as media study of interest correctreading news. This Development CD interaktif is gone through to pass/through 6development phase, start teoretis analysis test use of product. Source of data researchof this development entangle 5 people learn Javanese and 40 student people. ValidasiResearch of development entangle 5 items expert people as items validasi and mediaexpert as items validasi. yielded Product type in the form of CD interest interaktifcorrect reading news, in presentation format. Respon to CD interaktif developmentstudy of interest correct reading news obtained by result 2,5% disagree and rest isagreing and very agree. Result of research can be exploited as one of the alternativerepair of study media development as according to provided by facility school.Kata Kunci : kompetensi, menyimak, dan interaktif